2002
DOI: 10.4315/0362-028x-65.4.659
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Mathematical Models for Predicting Staphylococcus aureus Growth in Cooked Meat Products

Abstract: The growth of Staphylococcus aureus in commercially available vacuum-packaged cooked ham, turkey breast meat, and chicken breast meat stored at 2.3, 6.5, 10, 13.5, and 17.7 degrees C was studied. Growth rates observed in these food products were compared with those predicted on the basis of various growth models found in the literature and with those generated by the Pathogen Modeling Program and the Food MicroModel software using graphical and mathematical analysis for performance evaluation. In general, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 41 publications
2
18
0
Order By: Relevance
“…108 However, predictive models cannot be used as the sole determinant of product safety. 109 If important decisions are to be made based on the results of a predictive model it must be validated in the food of interest.…”
Section: Risk Assessment and Predicitive Microbiology To Control Entementioning
confidence: 99%
“…108 However, predictive models cannot be used as the sole determinant of product safety. 109 If important decisions are to be made based on the results of a predictive model it must be validated in the food of interest.…”
Section: Risk Assessment and Predicitive Microbiology To Control Entementioning
confidence: 99%
“…Data used in building a model are usually acquired in laboratory media. However, the predictions agree more or less successfully with observations of food products (6,36), and validation of the model proves to be necessary in such cases. Salter et al (31) underlined the importance of good prediction for food safety, although their model was not validated in their paper.…”
mentioning
confidence: 80%
“…The mean lag time predicted by PMP was 19.0 h (95% CI of 14.2 to 25.5 h), which is longer than that estimated by the BP dec method (10.4 h [ Table 4]). In comparison, Castillejo-Rodriguez et al (8) reported a lag time of 40 h for S. aureus in a cooked chicken meat product stored at 17.7°C.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments were performed at 17°C in a broth simulating the reported properties of a cooked cured chicken meat product (8), chicken broth. The chicken broth was prepared using brain heart infusion (BHI) broth (Difco) as a base with pH, water activity (a w ), and concentrations of salts adjusted to the values reported previously (8). To achieve the desired a w , glycerol was used in addition to NaCl as a humectant.…”
Section: Methodsmentioning
confidence: 99%